2016
DOI: 10.3390/app6120401
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Process Parameters on the Surface Roughness of a 3D-Printed Co–Cr Dental Alloy Produced via Selective Laser Melting

Abstract: Selective laser melting (SLM), used to fabricate metallic objects with high geometrical complexity, is currently of increasing interest to the fields of medicine and dentistry. SLM-fabricated products should have highly smooth surfaces to minimize the use of post-processing procedures such as finishing and polishing. This study investigated the effect of various laser process parameters (laser power, scan rate, and scan-line spacing) on the surface roughness of a Co-Cr dental alloy that was three-dimensionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…This process has been used successfully to fabricate parts made of titanium alloys [10], stainless steel [11], CoCrMo alloys [12,13], and copper alloys [14]. In SLM, a continuous molten track needs to be formed in order to achieve densification.…”
Section: Introductionmentioning
confidence: 99%
“…This process has been used successfully to fabricate parts made of titanium alloys [10], stainless steel [11], CoCrMo alloys [12,13], and copper alloys [14]. In SLM, a continuous molten track needs to be formed in order to achieve densification.…”
Section: Introductionmentioning
confidence: 99%
“…The laser additive manufacturing (LAM) process which fabricates Ti-6Al-4V titanium alloy with a near net shape has no restriction in the component shapes. It has been popular in recent studies [4][5][6][7] and has been widely used to fabricate complex components in aerospace and other industries [1]. The typical grain structure in the fabricated Ti-6Al-4V titanium alloy samples is coarse columnar prior β grains, which arise due to high temperature gradients and distribute approximately parallel to the building direction [8].…”
Section: Introductionmentioning
confidence: 99%
“…2017, 7, 710 2 of 6 In addition, low surface quality (such as cracking, delamination, and swelling) is one of the major drawbacks encountered in the SLM process [5]. Hong et al [6] demonstrated that three laser process parameters (laser power, scan rate, and scan-line spacing) directly influenced the surface roughness of an SLM cobalt-chromium (Co-Cr) dental alloy. Yasa et al [5] suggested "laser re-melting," in which, after scanning a layer and melting the powder, the same slice is re-scanned before adding a new layer.…”
mentioning
confidence: 99%
“…However, the dimensional accuracy of the final 3D product can be significantly jeopardized by many factors, including thermal distortion due to continuous melting and resolidification during the SLM process [6]. Kim et al [7] reported that SLM-fabricated Co-Cr alloy copings showed significantly larger marginal discrepancies than cast ones.…”
mentioning
confidence: 99%
See 1 more Smart Citation